Bank oligopoly competition analysis using a differential equations model. (29th March 2020) - Chalikias, Miltiadis; Lalou, Panagiota; Skordoulis, Michalis; Papadopoulos, Perikles; Fatouros, Stavros
The purpose of this paper is to propose a model of differential equations that will be able to be applied in a bank oligopoly competition case. The differential equations model will be based on Lanchester's combat model, a well-known mathematical theory of war. Due to the fact that an oligopoly of four banks will be examined, the proposed model will consist of a 4x4 differential equations system. Many researchers have already concluded that mathematical theories of war models can be successfully applied to business cases as there are many similarities between the battle fields and the business competition. Since the proposed model's predictions concern the deposits evolution, this model can contribute in the analysis of the competition between the four major banks in Greece. The statistical analyses carried out confirm the model's good fit.